Cumulonimbus tops around Bombay (MAUSAM, 1976)
Cumulonimbus clouds around Bombay observed during 1972-74 with the help of 3 cm BEL radar equipped with RHI, were studied. The study revealed that high Cb tops crossing tropopause generally occur 300 km away north and south of Bombay during pre-mosoon and post-monsoon seasons, Generally the tops did not exceed 12 km in height around 100 km of Bombay. It was also confirmed that the tops crossing tropopause with a fair degree of accuracy can be forecast on the basis of morning ascent using the method suggested by Mukherjee and Choudhury.